Evolutionary and Developmental Associations of Neural Crest and Placodes in the Vertebrate Head: Insights From Jawless Vertebrates - York, Joshua R. (Front Physiol, 2020)
Neural crest and placodes are key innovations of the vertebrate clade. These cells arise within the dorsal ectoderm of all vertebrate embryos and have the developmental potential to form many of the morphological novelties within the vertebrate head. Each cell population has its own distinct developmental features and generates unique cell types. However, it is essential that neural crest and placodes associate together throughout embryonic development to coordinate the emergence of several features in the head, including almost all of the cranial peripheral sensory nervous system and organs of special sense. Despite the significance of this developmental feat, its evolutionary origins have remained unclear, owing largely to the fact that there has been little comparative (evolutionary) work done on this topic between the jawed vertebrates and cyclostomes—the jawless lampreys and hagfishes. In this review, we briefly summarize the developmental mechanisms and genetics of neural crest and placodes in both jawed and jawless vertebrates. We then discuss recent studies on the role of neural crest and placodes—and their developmental association—in the head of lamprey embryos, and how comparisons with jawed vertebrates can provide insights into the causes and consequences of this event in early vertebrate evolution.